The Routledge companion to Indian ethics: women, justice, bioethics and ecology - Bilimoria, Puruṣottama; Rayner, Amy (Routledge, Taylor & Francis Group, 2024)
"This companion volume focuses on the application and practical ramifications of Indian ethics. It reports on contemporary wide-ranging social and communal challenges facing people in such diverse areas as women and ethics, politics, justice, bioethics and ecology. As a contemporary volume, it builds linkages between existing theories and emerging issues, problems and questions in today's India. The volume brings together contributions from philosophers and contemporary thinkers on practical ethics, exploring both the scope as well as boundaries or limits of ethics when applied to everyday and real-life concerns and challenges facing India in the context of a troubled globalizing world. As such, this collection draws on multiple forms of writing and research, including classical essay form, reportage and interview, critical case studies and textual analyses The book will be of interest to scholars, researchers and students of Indian philosophy, Indian ethics, women's issues, social justice, environmental ethics, bioethics, animal ethics, and cross-cultural responses to dominant Western moral thought. It will also be useful to researchers working on Gandhi, sustainability, ecology, comparative philosophy, and dharma studies"--